PEMBINAAN KARAKTER KEWARGANEGARAAN MULTIKULTURAL DI PONDOK PESANTREN AL MUQODASAH PONOROGO - Kurniawan, Bekti Galih; Marzuki (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Diversity in Indonesia creates conflict and social inequality. Islamic boarding schools are educational institutions that can build diversity. This study aims to analyze the development of multicultural citizenship. This study uses a qualitative research design and incredibly descriptive phenomenological research. The data sources in this study were the head of the Islamic boarding school, the citizenship teacher, and the scout coach. Data collection techniques using interviews, observation, and documentation. In addition, the data validity technique uses triangulation. Data analysis used Miles & Huberman qualitative analysis technique. The results of this study are the pesantren culture in fostering the character of multicultural citizenship. Namely, students must obey the rules, wear the same uniform as a symbol of equality among students, and Islamic boarding schools provide several extracurricular activities to maximize student activities. It is concluded that the development of multicultural citizenship character is carried out by Civics teachers who are involved in the use of learning models, approaches, and examples through pesantren culture such as pesantren and school rules, routine activities, role models, and extracurricular programs. Through extracurricular scouts in the form of scouting rules, routine activities, and examples.